Main problems experienced by the neighbors of open drug scenes, Tehran, Iran: a mixed-method study - Sahar Eshrati; MohammadBagher Saberizafarghandi; Meroe Vameghi; Reza Arezoomandan; Hadi Ranjbar; Thomas Clausen; Helge Waal (BMC, 2023)
Abstract Background Despite law enforcement and health interventions, open drug scenes have led to problems in many countries. The problems are, however, insufficiently explored. There are different types of drug scenes in Iran. This study aimed to explore the issues related to neighbors of one of the drug scenes in Tehran known as Farahzad. Methods Data were generated via semi-structured interviews in the first step of the current mixed-method study (2020-2021). Interviewees were people who use drugs (PWUDs), residents and business owners (N = 25). In the next step, a quantitative observation was conducted for eight days. The results were analyzed using conventional content analysis and descriptive statistics. Results The perceived problems were ambivalent attitudes about drug scene-related activities, violate of the territory of the self of the effected residents, and everyday concerns. The observation results indicated that men who use drugs are involved in drug scene-related activities more than women are. PWUDs try to hide their activities from the public view. Their efforts were considered "self-regulatory strategies" in the drug scene. Conclusions Despite efforts of PWUDs to keep their activities invisible, drug scene-related issues are intolerable for neighbors. Neighbors and PWUDs have ambivalent attitudes. While they are concerned about the human rights of each other, drug scene-related activities have disturbed the neighbor's daily life and economic activities. Although law enforcement and harm reduction interventions reduce some of the problems, one of the approaches should be improving the coexistence between the neighbors and the residents of the drug scene to achieve broader and more sustainable compromises.